3D Binder‐free Integrated Electrodes Prepared by Phase Separation and Laser Induction (PSLI) Method for Oxygen Electrocatalysis and Zinc–Air Battery. Issue 25 (10th May 2022) - Sha, Yang; Peng, Yudong; Huang, Kun; Li, Lin; Liu, Zhu
Abstract: Developing facile approaches to fit in large‐scale fabrication of efficient and durable catalytic electrodes is highly desirable for oxygen electrocatalysis and metal–air batteries. Herein, a strategy based on phase separation and laser induction is proposed to prepare 3D binder‐free integrated electrodes (IEs). The phase separation between a polybenzimidazole (PBI) solution and a coagulation bath containing metal precursors occurs to form a 3D interconnected porous catalyst precursor layer. After drying, IEs are obtained by laser induction, which simultaneously converts PBI into hierarchically porous laser‐induced graphene (HPLIG) and reduces metal precursor to tiny nanoparticles. To demonstrate the versatility of this method, IEs with different HPLIG hybrid catalyst layers and substrates are fabricated. IE‐NiFe/HPLIG and IE‐Co/HPLIG using carbon paper as a substrate exhibit superior oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) performance respectively. Flexible IE‐NiCoFe/HPLIG with OER and ORR bifunctionality using carbon cloth as the substrate is applied as an air cathode in rechargeable aqueous Zinc–air batteries (ZABs) and provides a satisfactory power density of 163 mW cm −2 and cycling stability of 1800 h at 10 mA cm −2 . The electrode also endows solid ZABs with good flexibility. This work offers an industrially viable solution to the challenge of rapid fabrication of IEs. Abstract : In this study, for the first time, a strategy based on phase separation and laser induction is applied to prepare 3D‐binder free integrated electrodes (IEs) for electrocatalysis. Benefiting from the 3D interconnected hierarchically porous structures of catalyst layers and spatial confinement effects of laser induced graphene for nanopaticles, IEs exhibit promising activity and stability in oxygen electrocalysis and zinc‐air batteries.